Decomposition-based evolutionary optimization in complex environments - Li, Juan (World Scientific, 2020)
"Multi-objective optimization problems (MOPs) and uncertain optimization problems (UOPs) which widely exist in real life are challengeable problems in the fields of decision making, system designing, and scheduling, amongst others. Decomposition exploits the ideas of 'making things simple' and 'divide and conquer' to transform a complex problem into a series of simple ones with the aim of reducing the computational complexity. In order to tackle the abovementioned two types of complicated optimization problems, this book introduces the decomposition strategy and conducts a systematic study to perfect the usage of decomposition in the field of multi-objective optimization, and extend the usage of decomposition in the field of uncertain optimization"--Publisher's website
Keywords: Evolutionary computation; Multiple criteria decision making